Diabetes and dementia – the two faces of Janus - Papazafiropoulou, Athanasia K. (Arch Med Sci Atheroscler Dis, 2020)
Patients with type 2 diabetes are at high risk for cognitive decline and dementia. Despite the limited data on the possible pathogenetic mechanisms, evidence suggests that cognitive decline, and thus dementia and Alzheimer’s disease, might arise from a complex interplay between type 2 diabetes and the aging brain, including decreased insulin signalling and glucose metabolism, mitochondrial dysfunction, neuroinflammation, and vascular disease. Furthermore, there is increasing interest on the effects of antidiabetic agents on cognitive decline. There are many studies showing that antidiabetic agents might have beneficial effects on the brain, mainly through inhibition of oxidative stress, inflammation, and apoptosis. In addition, experimental studies on patients with diabetes and Alzheimer’s disease have shown beneficial effects on synaptic plasticity, metabolism of amyloid-β, and microtubule-associated protein tau. Therefore, in the present review, we discuss the effects of antidiabetic agents in relation to cognitive decline, and in particular dementia and Alzheimer’s disease, in patients with type 2 diabetes.